Maternal Employment and Breastfeeding: Results from the Longitudinal Study of Australian Children - Amir, L.H.; Cooklin, A R; Donath, S (My University, 2008)
Aim: To investigate the effect of maternal postnatal employment on breastfeeding duration in Australia in the first 6 months after birth. Method: Secondary data analysis of the infant data (2004) from the Longitudinal Study of Australian Children (LSAC). Complete maternal and breastfeeding data were available for 3697 infants. Multivariable logistic regression was used to investigate the effect of timing of resumption of maternal employment and maternal employment status on breastfeeding at 6 months postpartum after adjustment for maternal education, maternal age, maternal smoking during pregnancy and socioeconomic status of the child's area of residence. Results: Fewer women employed full-time were breastfeeding their infants at 6 months (39%) than nonemployed women (56%). Participation in full-time employment before 6 months had a strong, negative effect on the likelihood of continuing breastfeeding for 6 months, adjusted OR = 0.35 (95%CI: 0.22–0.55). Compared to nonemployed women, fewer women in part-time employment were breastfeeding at 6 months (44%), adjusted OR = 0.49 (95% CI: 0.37–0.64). Conclusions: Results from this large representative cohort of Australian infants confirm that maternal employment in the first 6 months of life contributes to premature cessation of breastfeeding even when known risk factors for breastfeeding cessation are controlled for.
Acta Paediatrica
Keywords: Families; Health -- Breastfeeding; Families -- Mothers; Employment; Health; Families and relationships; Health and wellbeing; Labour market; Health; Employment; Families; Mothers; Breastfeeding; Employment and unemployment; Families and relationships; Health and wellbeing